Atypical hand foot mouth disease presenting as vesiculobullous lesion - Lohidakshan, Nihil E.; Srinivas, Chakravarthi R.; Alanghat, Sruthi (International Journal of Contemporary Pediatrics, 2021)
Hand, food, and mouth disease (HFMD) is a highly contagious disease caused by enteroviruses affecting young children under 5 years. Among enteroviruses (EVs), the main pathogens of HFMD are coxsackievirus A16 (CV-A16) and EV-A71 (EV-71).1 The clinical features include a prodromal phase which has low-grade fever, malaise and sore throat. This initial phase is usually followed by enanthem and erythematous papular skin lesions, predominantly affecting palms and soles. The dorsal surface of hands, feet, and perioral skin are rarely affected. Atypical HFMD presents as a widely distributed rash with varying morphology that makes clinical diagnosis and treatment challenging.2 Our objective is to present atypical cutaneous manifestations of HFMD caused by CA6.